Gimme shelter: Social distancing and income support in times of pandemic - Aminjonov, Ulugbek; Bargain, Olivier; Bernard, Tanguy (International Food Policy Research Institute, 2021)
Strict containment limits the spread of pandemics but is difficult to achieve when people must continue to work to avoid poverty. A new role is emerging for income support: by enabling people to effectively stay home, it can produce substantial health externalities. We examine this issue using data on human mobility and poverty rates in 729 subnational regions of low- and middle-income countries during the first year of COVID-19. Shelter-in-place orders decrease work-related mobility in general, but much less so in the poorest regions. Emergency income support significantly mitigates this mobility gap between regions. It reduces by half the additional contagion caused, via the mobility channel, by regional poverty differences.